Direct Asymmetric Friedel–Crafts Reaction of Naphthols with Acetals Catalyzed by Chiral Brønsted Acids - Qin, Long; Wang, Pei; Zhang, Yixin; Ren, Zhengxiang; Zhang, Xin; Da, Chao-Shan (Synlett, 2016)
The Friedel–Crafts method synthesis of chiral ethers from various acetals and naphthols catalyzed by chiral Brønsted acids with acetic acid as an effective additive is described. We found that the chiral phosphoric acid (R)-TRIP could efficiently catalyze the asymmetric Friedel–Crafts reaction of naphthols with acetals affording chiral ethers in good enantioselectivity and yield.
Keywords: Friedel–Crafts reaction; chiral ethers; acetals; chiral Brønsted acid; asymmetric organocatalysis